Efektivasi Pengumpulan Zakat di Kabupaten Sumbawa Barat - Amir Ma’ruf Ma’ruf (Faculty of Economics and Management, 2022)
The potential for zakat in Indonesia is very huge, in 2019 it reached Rp 233,8 trillion but the collection by the zakat management organization (ZMO) is very small, only around 3.2%. This phenomenon occurs both at the national and regional scales. KSB is one of the areas in Indonesia with a majority Muslim population, where out of 159.980 prosperous people, 98,44% are Muslims. This situation illustrates the potential for zakat in KSB. However, the phenomenon found in the field is the opposite. From the result of research on this phenomenon, four factors were found, namely awareness of muzakki, trust in ZMO, work scope of WMO, and small incentives for muzakki. To increase the effectiveness of zakat collection, an intervention is needed. This research is a qualitative research using the Susamto’s Four Fields as an analytical tool. The result found that the most likely form of intervention to be carried out was in the form of providing additional incentives for muzakkis who had paid their zakat. This insentive is not from areduction in the total zakat collection, but from other thing that can continue to trigger the spirit of muzakki. This effectiveness program must be institutionalized with support from the government.